Next-Gen Composites: Impact of Nanopolypropylene on Carbon-Basalt Fiber Reinforced Hybrids - V. Chandran; N. Lenin; Lenka Čepová; D. Rajesh; Jan Blata; M. Siva Kumar; Muniyandy Elangovan (Journal of Natural Fibers)
The objective of this investigation is to develop novel interlaminated hybrid composites for the fabrication of battery outer casing. In this work, the mechanical and morphological analyses of different proportions of nanopolypropylene particles reinforced interlaminated hybrid composites are investigated and compared with the results of pure hybrid fiber composite laminates. The nanopolypropylene particles reinforced interlaminated hybrid composites have different stacking of basalt and carbon fiber fabrics in CBCBC and BCBCB pattern, respectively. By way of hand lay-up and press molding, these laminates were fabricated. The compositions of nanopolypropylene particles varied from 2 wt.% to 10 wt.% in carbon fiber and basalt fiber fabric-based composites, along with epoxy and hardener. The results showed that sample code C1 showed better performance, consisting of 3 layers of carbon fiber and two layers of basalt fiber fabrics with 6 wt.% of polypropylene particles. The comparison study was also carried out with a pure polypropylene sheet. Further, the regression is identified through Minitab software to predict the mechanical analysis. These predicted values have a minimum deviation from the experimental values. In addition, variance analyses are performed to identify the maximum contribution of the input factor, which enhances the above-said mechanical properties.